Overview on performance degradation behavior of 20Cr25NiNb steel for gas cooled reactor cladding during service - Shu, Ming; Sun, Yongduo; Zhou, Qin; Xiao, Jun; Ma, Zhaodandan; Liu, Xiao (Frontiers in Materials, 2022)
In this paper, the performance degradation behavior of fuel cladding material 20Cr25NiNb for the British Advanced Gas Reactor (AGR) is reviewed in detail, which is a strong guideline for the material selection of supercritical carbon dioxide cooled reactors. The degradation behavior during in-core service mainly includes high-temperature creep, thermal aging and mechanical property degradation caused by neutron irradiation (fission gas products, helium embrittlement and irradiation sensitization) and CO2 (oxidation and carburizing). Long-term service in AGR leads to coarsening of the second phase and precipitation of harmful phases such as σ, leading to performance degradation of the cladding. A point that should require special attention is that intergranular stress corrosion cracking (IGSCC) and intergranular attack (IGA) problems occur during wet storage of spent fuel.